Validation of Bioavailability‐Based Toxicity Models for Metals. (27th December 2019) - Garman, Emily R.; Meyer, Joseph S.; Bergeron, Christine M.; Blewett, Tamzin A.; Clements, William H.; Elias, Michael C.; Farley, Kevin J.; Gissi, Francesca; Ryan, Adam C.
Abstract: Regulatory jurisdictions worldwide are increasingly incorporating bioavailability‐based toxicity models into development of protective values (PVALs) for freshwater and saltwater aquatic life (e.g., water quality criteria, standards, and/or guidelines) for metals. Use of such models for regulatory purposes should be contingent on their ability to meet performance criteria as specified through a model‐validation process. Model validation generally involves an assessment of a model's appropriateness, relevance, and accuracy. We review existing guidance for validation of bioavailability‐based toxicity models, recommend questions that should be addressed in model‐validation studies, discuss model study type and design considerations, present several new ways to evaluate model performance in validation studies, and suggest a framework for use of model validation in PVAL development. We conclude that model validation should be rigorous but flexible enough to fit the user's purpose. Although a model can never be fully validated to a level of zero uncertainty, it can be sufficiently validated to fit a specific purpose. Therefore, support (or lack of support) for a model should be presented in such a way that users can choose their own level of acceptability. We recommend that models be validated using experimental designs and endpoints consistent with the data sets that were used to parameterize and calibrate the model and validated across a broad range of geographically and ecologically relevant water types. Environ Toxicol Chem 2019;39:101–117. © 2019 SETAC